Pengambilan Gambar dan Penyuntingan Gambar dalam Program Televisi “Berkah Islami” Kompas TV Jawa Tengah - Erlinda Puspita Wardani; M.Bayu Widagdo (Interaksi Online, 2020)
Television is a mass media which until now as a highest penetration media in Indonesia. Television serve a lot of programs that entertain and also informative, so there must be a competition between television station in the making of good programs that loved by the people to get high rating. One of programs which loved is Islamic program. “Berkah Islami” is a TV Islamic program that discussedethic and manners in Islam. During the production process, of course the role of cameraman is really needed to get the videos which fulfill standards and directions of program director and also can explain the scripts in segment 1, 2, and 3. Not only that, to get a TV program with 3 segments, it also need the role of editor to make the program to be interesting and informative, so the editing should be following the directions, format, and concept from sutradara and scriptwriter. TV program “Berkah Islami” has a show schedule at 05.00 WIB every Sunday morning on Kompas TV Jawa Tengah. Release on 1st September 2019 until 24th November 2019.